نحو منهج لغوي مقصدي في التعامل مع نصوص الوحي: (Toward an Intentional Linguistic Methodology in Understanding the Revelational Scripture) - أحمد شيخو عبد السلام (At-Tajdid - Intellectual Refereed Journal, 2022)
-